PLURALISME HUKUM WARIS DI INDONESIA - Adelina Nasution (Hukum Keluarga Islam IAIN LANGSA, 2018)
Law of inheritance in Indonesia up to now in a pluralistic (diverse). In the territory of the Unitary Republic of Indonesia, various inheritance legal systems apply, namely customary inheritance law, Islamic inheritance law and Western inheritance law listed in Burgerlijk Wetboek (BW). This legal diversity is increasing because customary inheritance laws that apply in reality are not single, but also vary according to the form of society and the family system of Indonesian society. Keywords: Pluralism, inheritance, custom